3-Deep new displays render images you can almost reach out and touch. - Sullivan, A.
Research continues to develop volumetric displays that render images in a 3D space rather than on a flat screen, focusing on two main technological approaches to displaying solid images electronically. The first approach is known as swept volume, which uses a high definition projector or an array of lasers to bounce images off a screen that rotates so fast that the human eye perceives only a 3D image floating in space. The other approach involves an all solid-state design that uses a projector behind a stack of 20 liquid-crystal screens to create one solid image from a rapidly projected series of images. All these systems create 3D images that require no special eyewear, produce no eye fatigue or headaches, and are visible over a wide field of view from several meters away by many people. If all goes well, economies of scale could bring prices down to a point where all sorts of intriguing applications become possible.
Keywords: 3D display; Brain tumor; Carry-on bag; Product prototype; Satellite orbit